Glycerol waste to value added products and its potential applications - Chaitanya Reddy, Chilakamarry; Mimi Sakinah, A. M.; Zularisam, A. W.; Pandey, Ashok (Springer Link, 2021)
The rapid industrial and economic development runs on fossil fuel and other energy sources. Limited oil reserves, environmental issues, and high transportation costs lead towards carbon unbiased renewable and sustainable fuel. Compared to other carbon-based fuels, biodiesel is attracted worldwide as a biofuel for the reduction of global dependence on fossil fuels and the greenhouse effect. During biodiesel production, approximately 10% of glycerol is formed in the transesterifcation process in a biodiesel plant. The ditching of crude glycerol is important as it contains salt, free fatty acids, and methanol that cause contamination of soil and creates environmental challenges for researchers. However, the excessive cost of crude glycerol refining and market capacity encourage the biodiesel industries for developing a new idea for utilising and produced extra sources of income and treat biodiesel waste. This review focuses on the signifcance of crude glycerol in the value-added utilisation and conversion to bioethanol by a fermentation process and describes the opportunities of glycerol in various applications.